Is the association between various emotion-regulation skills and mental health mediated by the ability to modify emotions? Results from two cross-sectional studies - Berking, Matthias; Poppe, Christine; Luhmann, Maike; Wupperman, Peggilee; Jaggi, Verena; Seifritz, Erich (Journal of Behavior Therapy and Experimental Psychiatry, 2012)
Background and objectives: In order to clarify mechanisms underlying the association between emotion regulation and psychopathology, we tested whether the ability to modify negative emotions mediates the associations of other emotion-regulation skills with psychopathological symptoms in two studies. Methods: The first study included 151 college students; the second included 121 psychiatric inpatients. Bootstrapping-enhanced mediation analyses were utilized to assess associations between self-reports of emotion-regulation skills and psychopathology, as well as potential mediation effects. Results: In both samples, the ability to modify emotions completely mediated the association between symptoms and skills for most skills, but not for the skill of accepting/tolerating negative emotions. Limitations: Major limitations include the use of a cross-sectional design as well as exclusive use of self-report data. Conclusions: The ability to modify negative emotions may be the common pathway by which many emotion-regulation skills exert their influence on mental health; however, the skill of accepting/tolerating negative emotions may be beneficial to mental health regardless of whether or not it facilitates modification of emotions. © 2011 Elsevier Ltd. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Emotion regulation; Mediation; Psychopathology; Skills